Effects of Nanocrystal Cellulose from Bamboo on the Flexural Strength of Acrylic Resin: In Vitro - Visakha Aupaphong; Kriangsak Kraiwattanawong; Bhornsawan Thanathornwong (My University, 2022)
The purpose of this study is to evaluate the effects of nanocrystal cellulose (NCC) from bamboo on the flexural strength of heat-cured acrylic resin. A total of 35 specimens (3.3 mm × 10 mm × 64 mm) were prepared and the specimens were divided into five groups of seven specimens each. Group 1 used conventional acrylic resin that was prepared based on the instructions of the manufacturer (0%). The filled NCC from bamboo fiber in four concentrations (0.25, 0.5, 1, and 2% w/w) was used in the four-reinforcing resin workpiece groups. The specimens were loaded until failure occurred on a three-point bending test machine. One-way analysis of variance and Dunnett’s multiple comparison test at a 95% confidence level were used to determine the statistical differences in the flexural strength among the five groups. The results found that the average flexural strength of five specimen groups (0, 0.25, 0.5, 1, and 2% w/w) were 60.11 ± 2.4, 60.75 ± 2.18, 66.50 ± 5.08, 56.04 ± 0.31, and 48.05 ± 2.61 MPa, respectively. The flexural strength of 0.5 mg% w/w NCC-reinforced acrylic resin was significantly higher than the control group (p < 0.01). The reinforced NCC from bamboo fiber to acrylic resin improved the flexural strength properties.
Keywords: Acrylic resin; Advanced Cellulose Research Studies